Dynamic interaction of spliceosomal snRNPs with coilin explains Cajal body characteristics - Basello, Davide A; Blažíková, Michaela; Roithová, Adriana; Hálová, Martina; Radivojević, Nenad; Neugebauer, Karla M; Staněk, David (The Journal of cell biology, 2025)
The Cajal body (CB) is a conserved non-membrane nuclear structure where several steps of small nuclear RNP particle (snRNP) biogenesis take place. It has been proposed that CB formation follows a liquid-liquid phase separation model, but this hypothesis has never been rigorously tested. Here, we applied live-cell imaging to show that the key CB assembly factor coilin is mobile within the CB, and we revealed a diffusion barrier that limits the coilin exchange between CBs and the nucleoplasm. We generated single aa mutations and demonstrated that RNA-dependent coilin oligomerization and coilin interaction with snRNP are essential for CB formation and maintenance. We applied these data to formulate a mathematical model that links the movement of coilin within the nucleoplasm, CB, and across the boundary with its oligomerization and snRNP binding. Our results illustrate CB as a structure dynamically responding to snRNP assembly and recycling.
Keywords: Spliceosomes; Protein Binding; HeLa buňky; Coiled Bodies; spliceozomy; vazba proteinů; Cajalova tělíska; mutace; ribonukleoproteiny malé jaderné; jaderné proteiny; lidé; multimerizace proteinu; Mutation; Nuclear Proteins; HeLa Cells; Humans; Protein Multimerization; Ribonucleoproteins, Small Nuclear